Pilot Investigation: Older Adults With Atrial Fibrillation Demonstrate Greater Brain Leukoaraiosis in Infracortical and Deep Regions Relative to Non-Atrial Fibrillation Peers - Wiggins, Margaret E.; Jones, Jacob; Tanner, Jared J.; Schmalfuss, Ilona; Hossein Aalaei-Andabili, Seyed; Heilman, Kenneth M.; Libon, David J.; Beaver, Thomas; Price, Catherine C. (Frontiers in Aging Neuroscience, 2020)
Background: This pilot study explored differences in distribution of white matter (called leukoaraiosis; LA) in older adults with atrial fibrillation (AF) vs non-AF peers measured by 1) depth distribution; 2) anterior-posterior distribution; 3) associations between LA and cortical thickness; and 4) presence of lacunae and stroke. Methods: Participant data (AF n=17; non-AF peers n=17) were acquired from federally-funded investigations with the same neuroimaging protocols. LA volume was quantified by cortical depth (periventricular, deep, infracortical) and in anterior and posterior regions. Cortical thickness by lobe was assessed relative to LA load. Results: Relative to non-AF peers, the AF group had twice the total LA (2.1% vs. 0.9%), over ten times greater infracortical LA (0.72% vs. 0.07%), and three times greater deep LA (2.1% vs 0.6%). Examinations of anterior versus posterior LA load did not reach significance, though there was a trend for more posterior relative to anterior LA in the entire sample (p=0.088). In the entire sample, total LA and infracortical LA were negatively associated with temporal lobe thickness. Only those with AF presented with lacunae or stroke. Conclusions: Older adults with AF had more total white matter disease than those without AF, particularly near the cortical mantle and deep within the cortex. Total and infracortical white matter disease in the entire sample negatively associated with temporal lobe thickness. Results suggest that those with AF have a distinct pattern of LA relative to those without AF, and that LA severity for all individuals may associate with structural changes in the cortex.